DATA KESETIMBANGAN UAP-AIR DAN ETHANOL-AIR DARI HASIL FERMENTASI RUMPUT GAJAH - Sari, Ni Ketut (Jurnal Teknik Kimia, 2012)
The high purity of ethanol (Pro Analitic) commonly used for row material to get the VLE Value, but the research used the technical ethanol that from distillation of the product bulrush  fermentation. The research purpose to find the value of VLE on the binary system ethanol-water. Then the result compared with literature. Still othmer glass was used as main device and the row material from high purify ethanol (PA) and moderate. Moderate Purity ethanol (Technical ethanol). These row material combine with various composition are 0; 0,2 ; 0,4 ; 0,6 ; 0,8 ; 1 (mole Fraction) and constant  pressure 300 bar. Next, the product was analyzed by spectrophotometer pharo 100. Then the result was compared with literature value and show that the value close to the literature value. From the VLE curve show that the azeotropic point in the composition of ethanol 0,98 (molefraction) Keywords : Azeotropes, azeotropic point, bulrush, VLE on the binary system ethanol-water,